KEPEMILIKAN JAMBAN SEHAT DENGAN KEJADIAN DIARE PADA BALITA DI DUSUN KLIWON DESA CIBINGBIN KECAMATAN CIBINGBIN - RIZQI, ALFIANI (Jurnal Ilmiah Dozen Globalindo, 2021)
One of the health efforts carried out in the community is the provision of basic sanitation, one of the few basic sanitation facilities in the community is a healthy toilet. Based on WHO data in 2010, it is estimated that 1.1 billion people or 17% of the world's population still defecate in open areas, from the data above, 81% of the population who defecate in open defecation (BABS) is found in 10 countries and Indonesia as a country. second most people found defecating in open areas. Based on data obtained from the Kuningan District Health Office, the lowest coverage of healthy latrines is Cibingbin District, 68.48%. Knowing the relationship of ownership of healthy latrines in Kliwon Hamlet, Cibingbin Village, Cibingbin District. The type of research used for this research is quantitative research using analytical research design and cross sectional design. The sample in this study were all residents who have children under five in Kliwon Hamlet, Cibingbin Village, Cibingbin Village, as many as 67 respondents who were taken by random sampling technique. Cross tabulation of the relationship between the independent and dependent variables with the Chi Square statistical test. Chi Square analysis of the relationship between ownership of healthy latrines and the incidence of diarrhea in children under five was obtained p value = 0.003 <0.005. There is a relationship between having healthy latrines and the incidence of diarrhea among children under five in Kliwon Hamlet, Cibingbin Village. It is expected that respondents who have toddlers pay attention to environmental cleanliness and get used to using healthy latrines so that they can prevent diarrhea in toddlers.